AS MULHERES NA INDÚSTRIA: ESTUDO DAS REPRESENTAÇÕES SOCIAIS E ESTRATÉGIA COMO PRÁTICA SOCIAL - Santos, Carla (2019)
This dissertation is related to: Social representation of women who work in factory with management position and how they participate in the organization strategy, it is about Strategy research line, from the Master's degree in Administration Program, Professional Master’s Degree in Administration at UNICENTRO. Changings occurred in the last decades about the relationship among people have had a new form, it is reflexing on market structure of work. It is known that even each more in the women history at organizations have been rewrite due to their transformations and visibility on contemporary society. All this context must inflict the need to know how women represent themselves, how observe themselves as managers and in what way plan their routine activities at the organizations. Related to Social Representation Theory it was aimed, as general goal: comprehend, from on women perspective as employees of automobile factory in Curitiba, the social representation assigned by themselves referred to strategy action worked. Therefore, this study is a descriptive research with qualitative approach. To data collection, were done interviews with eight women in management position, in a factory of automobile field, located in a metropolitan region of Curitiba, Paraná state. It was used the content analyses technique, the data were analysed and interpreted by three analyses categories: a) woman in labour market linked with studies of Probst (2005), Perrot (2007) and Beauvoir (2009); b) strategy as social practice, structured on studies of Whittigton (1996,2002, 2006); Jarzabkowski (2007) and Carter (2008) and, finally, c) woman representation in management position, the theory base was from Moscovici (1978), Jodelet (2001), Cappelle et al (2013). It is illustrated that women social representation researched is meaningful in all categories investigated. In the strategy actions and routines, the managers participate direct or indirectly of composed stages. As consequences from these process participation, it was identified the autonomy to taking a decision, the mangers as practitioners of strategies they demonstrate strong relations commitment to the organization, and when use interaction to executed activities, might demonstrate their thinking of who they are. In the social representation category of factory workers women, is observed in the interviews answers the convictions defence because they are women in management position. They represent themselves as women placed in the labour market with management position; that use their knowledge to manage their work group; that define, execute and spread strategy actions. Thus, the management model presented at the managers actions during the job routine are their objects of social representation. Resulted from transformations of social representation in the female labour market, where even each more women assume management positions. In addition, the contribution to reduce the theory gap is about woman social representation issue from factory, in the strategy approach as social practice, responsible by strategy formulating from organizations. As practice contribution to organizations, the study allows better comprehension, from the own women voices, as paradigmatic changings about doing strategy in organizations have set, mainly related to women with management position, in order to organizations strategies, reflected in a positive way in all organizational process, without obstacles related to gender and productive capacity.